The Influence of Work Quality and Employee Competence on Human Resources Professionalism at the Ministry of Defense Planning and Finance Bureau - Pandji Sukmana; Azis Hakim (International Journal of Social Science and Business, 2023)
This study aims to analyze the effect of work quality and employee competence, individually and collectively, on the professionalism of human resources at the Planning and Finance Bureau of the Ministry of Defense. The research method uses a correlational survey with a quantitative approach; the sampling technique is simple random sampling, namely simple random sampling. The population in this study were employees, as many as 78 people. In contrast, the sample in this study was 65 respondents, with the percentage of inaccuracy determined to be as much as 5%. The results showed that: a) quality of work on the professionalism of human resources had a strong and significant positive influence with the results of a correlation coefficient of 58.6%, while other factors and tests influenced the remaining 41.4%. Significant (t-test) tcount 9,439 > ttable 2,000; b) employee competence on the human resource professionals has a strong and significant positive influence with the results of a correlation coefficient of 57.6% while the remaining 42.4% is influenced by other factors and significant test (t-test) tcount 9,247 > ttable 2,000; c) work quality and employee competence together on the professionalism of human resources has a strong and significant positive influence with a correlation coefficient of 61.8% while the remaining 38.2% influenced by other factors and significant test (F test) Fcount 50,073 > Ftable 3,15. The implication of this research is the importance of work quality and employee competence in increasing the professionalism of human resources in the Planning and Finance Bureau of the Ministry of Defence.